Effect of Torulaspora delbrueckii Yeast Treatment on Flavanols and Phenolic Acids of Chenin blanc Wines - Ngqumba, Z.; Ntushelo, N.; Jolly, N.P.; Ximba, B.J.; Minnaar, P.P. (South African Journal of Enology and Viticulture, 2017)
The non-Saccharomyces yeast Torulaspora delbrueckii contributes positively to the sensory properties of wines by affecting aroma and flavour due to changes in alcohols, esters, fatty acids and lactone levels. One of the less-studied aspects of T. delbrueckii is its effect on phenolic compounds relating to sensory attributes. An HPLC-DAD technique was used for the quantification of phenolic compounds in Chenin blanc wines made with S. cerevisiae and two T. delbrueckii yeasts over three vintages. Chemical and sensory data were subjected to ANOVA and PCA. VIN13, M2/1 and VIN13+M2/1 had a positive effect on the phenolic compound concentrations of Chenin blanc wines. Mouthfeel was highest in VIN13+654 wines and astringency highest in VIN13 wines. An association was evident between flavanols, astringency and mouthfeel for the VIN13, M2/1 and VIN13+M2/1 wines. Chenin blanc wines made with M2/1 and VIN13+M2/1 may result in increased phenolic compound concentrations and astringency, whereas 654 and VIN13+654 may result in wines with increased mouthfeel properties.